2012
DOI: 10.1111/j.1755-3768.2012.02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral optical coherence tomography findings in patients with ocular toxoplasmosis and active satellite lesions (MINAS Report 1)

Abstract: ABSTRACT.Purpose: To characterize the active retinochoroiditis lesion observed in patients with the classic clinical presentation of ocular toxoplasmosis (OT) utilizing spectral optical coherence tomography (SOCT). Methods: Twenty-four patients with OT and satellite lesions underwent standardized ophthalmologic examination and multimodal fundus imaging. The SOCT findings observed at presentation were described. Results: The mean age of the fourteen (58.3%) women and ten (41.7%) men was 27.6 years. The mean Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 27 publications
2
17
3
Order By: Relevance
“…Localized choroidal thickening has already been described in patients with ocular toxoplasmosis or choroidal tumors [8,9]; however, different from the choroidal bulging observed in this series of patients with VKH disease, an associated retinal or choroidal lesion was invariably observed in these scenarios on clinical exam (i.e., fundoscopy).…”
Section: Discussioncontrasting
confidence: 65%
“…Localized choroidal thickening has already been described in patients with ocular toxoplasmosis or choroidal tumors [8,9]; however, different from the choroidal bulging observed in this series of patients with VKH disease, an associated retinal or choroidal lesion was invariably observed in these scenarios on clinical exam (i.e., fundoscopy).…”
Section: Discussioncontrasting
confidence: 65%
“…In addition, thickening of the posterior hyaloid, hyperreflective signals, and spherical hyperreflective depositions in vitreous have been reported [8]. One-fifth of the patients were reported to have subretinal fluids at the lesion site [6,8]. We could demonstrate the active lesion in three of eight patients and see thickening of the retina at the lesion site, increased reflectivity of inner retinal layers, and posterior shadowing in all.…”
Section: Discussionmentioning
confidence: 56%
“…It has been reported that the retina was thickened at the lesion site, with an increased reflectivity of inner retinal layers and posterior shadowing [7]. In addition, thickening of the posterior hyaloid, hyperreflective signals, and spherical hyperreflective depositions in vitreous have been reported [8]. One-fifth of the patients were reported to have subretinal fluids at the lesion site [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Spectral-domain optical coherence tomography (SD-OCT) imaging is an important diagnostic tool to identify the morphological features of the vitreoretinal changes in ocular toxoplasmosis [39,40,41]. The stage of the disease is determinant for the SD-OCT findings of chorioretinal lesions.…”
Section: Clinical Featuresmentioning
confidence: 99%